Haynes 244 alloy with excellent high temperature oxidation resistance and preparation method thereof

By adding Ti and Al elements to the Haynes 244 alloy, a continuous chromium oxide layer and a dense oxide film are formed, which solves the problem of poor oxidation resistance of the alloy at high temperatures, and improves the service life and strong plasticity at high temperatures.

CN116815018BActive Publication Date: 2025-04-04NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310502593.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-04-04
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

Haynes 244 alloy has poor oxidation resistance at high temperatures and is difficult to meet the current demand for high-temperature service temperatures.

Method used

By adding Ti and Al elements to the Haynes 244 alloy, the atomic percentage ratio of Ti/Al is 0.9-1.2, which promotes the diffusion of Cr elements, forms a continuous chromium oxide layer, and inhibits the formation of TiN and reduces the peeling of the oxide layer.

Benefits of technology

During the oxidation process of 1000-1100 ℃ for 100 h, a dense oxide film is formed, which reduces the alloy oxidation rate, increases the service life of high temperatures, and has good strong plasticity at room temperature and 650 ℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116815018B_ABST
    Figure CN116815018B_ABST
Patent Text Reader

Abstract

The invention discloses a Haynes 244 alloy with excellent high-temperature oxidation resistance and a preparation method thereof. After microalloying, the alloy has good oxidation resistance at high temperature. The addition amount of Ti and Al in the alloy is Ti: 1%-3%, Al: 1%-3% by atomic percentage, and the balance is Ni. Wherein, when Ti / Al=0.9-1.2, the alloy has excellent high-temperature oxidation resistance. The present invention adopts vacuum induction melting to prepare the alloy. By adding Ti and Al elements, the alloy is oxidized in a muffle furnace at 1000°C and 1100°C for 100 h. Since Ti can promote the diffusion of Cr elements, continuous chromium oxide can be formed on the surface of the oxidized sample, and Al elements can inhibit the formation of TiN, thereby reducing the peeling of the oxide layer. Therefore, the addition of Ti and Al makes the oxide layer on the surface of the alloy more continuous, hinders the further diffusion of oxygen elements inward, reduces the oxidation rate of the alloy, and finds that the effect is better when Ti / Al is close to 1. Therefore, the improved Haynes 244 alloy of the present invention can be widely used in high-temperature environments, such as gas turbines, nuclear reactors, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature metal structural materials, and particularly relates to a Haynes 244 alloy with excellent high-temperature oxidation resistance and a preparation method thereof. Background Art

[0002] With the continuous development of the aerospace industry, metal materials suitable for turbine engines that are resistant to high temperatures, oxidation and creep have been continuously explored, and high-temperature alloys have gradually been proposed and developed. High-temperature alloys have high room temperature and high temperature strength, excellent fatigue resistance and creep resistance, good oxidation resistance and corrosion resistance. Therefore, high-temperature alloys are widely used in high-temperature components of aviation and aerospace engines, nuclear reactors, as well as ships, petrochemicals and other fields.

[0003] Haynes 244 alloy has been widely studied due to its excellent mechanical properties, oxidation resistance, creep properties and corrosion resistance. The good high temperature performance of Haynes 244 alloy is mainly due to the strengthening effect brought by various alloy elements, such as solid solution strengthening, precipitation strengthening, etc. However, with the development of various industries, the service temperature requirements of the required alloys are getting higher and higher. Haynes 244 alloy has poor oxidation resistance at high temperatures and can no longer meet the current use needs. Therefore, improving the oxidation resistance of Haynes244 alloy at high temperatures is an urgent problem to be solved. Summary of the invention

[0004] In view of the technical problems existing in the above background technology, the present invention provides a Haynes 244 alloy with excellent high-temperature oxidation resistance and a preparation method thereof, so that the Haynes 244 alloy forms a dense oxide film during oxidation at 1000-1100 ° C for 100 h to hinder the inward diffusion of oxygen elements, reduce the oxidation rate of the alloy, and improve the high-temperature service life of the alloy. The addition of Ti can promote the diffusion of Cr elements, and continuous chromium oxide can be formed on the surface of the oxidized sample, and the Al element can inhibit the formation of TiN, thereby reducing the peeling of the oxide layer.

[0005] The present invention is specifically implemented by the following technical solutions:

[0006] A first aspect of the present invention provides a Haynes 244 alloy having excellent high temperature oxidation resistance, wherein the addition amounts of Ti and Al in the Haynes 244 alloy are 1%-3% Ti and 1%-3% Al in atomic percentage.

[0007] As a further illustration of the present invention, the ratio of the Ti and Al additions is as follows, calculated in atomic percentage: Ti / Al=0.9-1.2.

[0008] As a further illustration of the present invention, the Haynes 244 alloy has an oxidation weight gain of <0.4 mg / mm after oxidation at 1100 °C for 100 h. 2 ; After oxidation at 1000 ℃ for 100 h, the oxidation weight gain is less than 0.7 mg / mm 2 .

[0009] As a further illustration of the present invention, during the oxidation process, continuous chromium oxide and aluminum oxide layers can be formed on the surface of the Haynes 244 alloy.

[0010] A second aspect of the present invention provides a method for preparing a Haynes 244 alloy having excellent high temperature oxidation resistance, comprising the following steps:

[0011] S1 According to the above Ti and Al addition amounts and the original composition ratio of Haynes 244 alloy, weigh the alloy raw materials and set them aside;

[0012] S2 arc-melting the weighed alloy raw material to obtain an alloy ingot, and then pouring it to obtain an alloy sample;

[0013] S3 taking out the alloy sample, performing homogenization annealing treatment, and then performing cold rolling treatment;

[0014] S4: performing recrystallization annealing on the alloy sample after cold rolling.

[0015] As a further illustration of the present invention, before smelting the Ti-containing alloy in S2, it is necessary to carry out 1-2 times of sponge Ti smelting in the side chamber of the smelting furnace for nitrogen fixation, so that there is no N in the smelting furnace during alloy smelting. 2 .

[0016] As a further illustration of the present invention, in the S2 smelting process, metal elements with similar melting points are first smelted together, and then the alloy ingots are smelted together 4 to 6 times.

[0017] As a further explanation of the present invention, the homogenization annealing treatment in S3 is specifically: placing the alloy sample in a heat treatment furnace for homogenization annealing treatment at 1180-1220° C. for 24 hours.

[0018] As a further illustration of the present invention, the total cold rolling deformation in S3 is not less than 70%, and the deformation in each pass is 2-10%.

[0019] As a further illustration of the present invention, the recrystallization annealing temperature in S4 is 1080-1120° C. and the time is 5-7 min.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] The invention provides a Haynes 244 alloy with excellent high-temperature oxidation resistance, wherein the addition of Ti element can promote the diffusion of Cr element, so that a continuous chromium oxide layer is formed on the surface of the oxidized sample, thereby better protecting the alloy matrix; the addition of Al element can inhibit the formation of TiN while forming an Al2O3 dense oxide layer, thereby reducing the peeling of the oxide layer.

[0022] When the Haynes 244 alloy with improved oxidation resistance provided by the present invention is used in a high temperature environment, a dense oxide film can be formed on the surface of the alloy to reduce the oxidation rate, and at the same time, the alloy has good strength and plasticity at room temperature and 650° C. Therefore, the improved Haynes 244 alloy of the present invention can be used in high temperature environments, such as gas turbines, nuclear reactors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The microstructures of the Haynes 244 alloys prepared in the embodiments of the present invention and the comparative examples are shown in FIG. Figure 1 (d) is the alloy structure after recrystallization annealing in the embodiment. Figure 1 (ac) are the alloy structures of comparative examples 1-5 after recrystallization annealing.

[0024] Figure 2 (a) and Figure 2 (b) is a comparison chart of the oxidation kinetic curves of the Haynes 244 alloy prepared in Comparative Examples 1-5 and the embodiment of the present invention at 1000°C and 1100°C.

[0025] Figure 3 (a) and Figure 3 (b) is the XRD pattern of the Haynes 244 alloys prepared in Comparative Examples 1-3 and the embodiments of the present invention after oxidation at 1000°C and 1100°C for 100h.

[0026] Figure 4 The figures are the oxidation cross-section energy spectra of the Haynes 244 alloys prepared in the embodiments of the present invention and the comparative examples, wherein (ac) are the oxidation cross-section morphologies and energy spectra of the comparative examples 1-3 alloys after oxidation at 1100°C for 100 h, and (d) is the oxidation cross-section morphology and energy spectra of the embodiment of the present invention alloy after oxidation at 1100°C for 100 h. Implementation

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] A Haynes 244 alloy with excellent high temperature oxidation resistance, wherein the addition amounts of Ti and Al in the Haynes 244 alloy are Ti: 1%-3%, Al: 1%-3% by atomic percentage; and the addition ratio of Ti and Al is as follows: Ti / Al=0.9-1.2 by atomic percentage. The original composition of the Haynes 244 alloy is shown in Table 1 below:

[0029] Table 1

[0030] Element Name Ni Cr Mo W Atomic percentage (%) 71.99 10.24 15.60 2.17

[0031] The Haynes 244 alloy with excellent high-temperature oxidation resistance provided by the present invention includes the following preferred single-element raw materials calculated by atomic percentage: Cr: 9%-11%, Mo: 15%-16%, W: 2%-3%, Ti: 0.9%-1.2%, Al: 0.9%-1.2%, and the balance is Ni.

[0032] The present invention can form a dense oxide film on Haynes 244 alloy during oxidation at 1000-1100°C for 100 h to hinder the inward diffusion of oxygen elements, reduce the oxidation rate of the alloy, and improve the high-temperature service life of the alloy. The addition of Ti can promote the diffusion of Cr elements, and continuous chromium oxide can be formed on the surface of the oxidized sample, and the Al element can inhibit the formation of TiN, thereby reducing the peeling of the oxide layer.

[0033] Specifically, the equilibrium structure of the Haynes 244 alloy with added Ti and Al elements provided by the present invention is an austenite matrix. And the oxidative weight gain of the Haynes 244 alloy after oxidation at 1100°C for 100 h is less than 0.4 mg / mm 2 ; After oxidation at 1000 ℃ for 100 h, the oxidation weight gain is less than 0.7 mg / mm 2 Furthermore, during the oxidation process of the Haynes 244 alloy at 1000°C and 1100°C, a continuous oxide layer can be formed on the surface, and the surface oxide peeling phenomenon is not obvious.

[0034] The preparation method of the above-mentioned Haynes 244 alloy having excellent high temperature oxidation resistance comprises the following steps:

[0035] S1 According to the above-mentioned Ti and Al addition amounts and the original composition ratio of Haynes 244 alloy, the atomic percentage is converted into mass percentage, and the alloy raw materials are weighed with a high-precision balance, and then ultrasonically cleaned with alcohol.

[0036] S2 Place the weighed alloy raw materials in a vacuum induction arc melting furnace for melting. To ensure uniform composition after melting, melt 4-6 times. After obtaining the ingot, use a 60×20×6 mm 3 Copper mold for pouring.

[0037] S3 The alloy sample obtained in S2 is taken out. In order to eliminate the defect of uneven cast structure, the alloy sample is placed in a heat treatment furnace for homogenization annealing at 1180-1220°C for 24 hours, and then cold rolled to refine the grains and improve the alloy properties.

[0038] S4 In order to eliminate the internal stress of the alloy after cold rolling, the cold rolled alloy sample was subjected to recrystallization annealing.

[0039] Preferably, before smelting the Ti-containing alloy in S2, it is necessary to perform 1-2 times of sponge Ti smelting in the side chamber of the smelting furnace for nitrogen fixation, so that there is no N in the smelting furnace during alloy smelting. 2 , preventing the generation of TiN in the original organization.

[0040] Preferably, in the smelting process in S2, since the melting points of the alloy elements differ greatly, in order to ensure uniform distribution of the components of the smelted sample, the metal elements with similar melting points are first smelted together, and then the alloy ingots are smelted together for 4 to 6 times.

[0041] Preferably, the total cold rolling deformation in S3 is not less than 70%, and the deformation in each pass is 2-10%.

[0042] Preferably, the recrystallization annealing temperature in S4 is 1080-1120° C. and the time is 5-7 min.

[0043] It should also be noted that when the recrystallization annealed sample obtained by S4 was subjected to subsequent characterization and oxidation experimental treatment, the oxidation temperature was 1000-1100 °C, the oxidation time was 1-100 h, and oxidation was performed in an air atmosphere using a muffle furnace.

[0044] The following is explained in conjunction with specific embodiments and comparative examples: Example

[0045] The ratio of atomic percentage of Cr: 10.04%, Mo: 15.32%, W: 2.15%, Ti: 1%, Al: 1% and the balance of Ni is converted into mass percentage and the single substance raw material is weighed.

[0046] Then, the sponge Ti and the above raw materials are placed in different slots of the vacuum induction arc melting furnace for melting and preparation according to their different melting points (those with similar melting points are placed in one slot). First, the sponge titanium is melted 1-2 times to remove the nitrogen in the furnace to prevent the generation of TiN in the original structure. After removing the nitrogen in the furnace, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4-6 times, and electromagnetic stirring must be accompanied during the preparation process. The alloy ingot is cast in a copper mold in a vacuum induction arc melting furnace to obtain a plate-shaped sample.

[0047] The plate alloy was then placed in a heat treatment furnace at 1200 °C for 24 h for homogenization annealing, and then the annealed alloy was cold rolled with a reduction of 75% to reduce the alloy thickness from 6 mm to 1.5 mm.

[0048] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100 °C for 5 min and then taken out and water-cooled.

[0049] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (d) The remaining samples were subjected to subsequent oxidation and other tests.

[0050] Comparative Example 1

[0051] The atomic percentages of Cr: 10.24%, Mo: 15.60%, W: 2.17%, and the balance Ni are converted into mass percentages and weighed.

[0052] Then, the above raw materials are placed in a vacuum induction arc melting furnace for melting and preparation according to their melting points (those with similar melting points are placed in one tank). First, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4 to 6 times. Electromagnetic stirring must be accompanied during the preparation process. The alloy ingot is cast in a copper mold in a vacuum induction arc melting furnace to obtain a plate-shaped sample.

[0053] The plate alloy was then kept at 1200°C for 24 hours in a heat treatment furnace for homogenization annealing, and then the annealed alloy was cold rolled with a reduction of 75% to reduce the alloy thickness from 6 mm to 1.5 mm.

[0054] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100°C for 5 minutes and then taken out and water-cooled.

[0055] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (a). The remaining samples were subjected to subsequent oxidation and other tests.

[0056] Comparative Example 2

[0057] The atomic percentages of Cr: 10.04%, Mo: 15.32%, W: 2.15%, Ti: 2%, and the balance Ni are converted into mass percentages and weighed.

[0058] Then, the sponge Ti and the above raw materials are placed in different slots of the vacuum induction arc melting furnace for melting and preparation according to their different melting points (those with similar melting points are placed in one slot). First, the sponge titanium is melted 1-2 times to remove the nitrogen in the furnace to prevent the generation of TiN in the original structure. After removing the nitrogen in the furnace, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4-6 times. Electromagnetic stirring must be accompanied during the preparation process.

[0059] The alloy ingot was cast using a copper mold in a vacuum induction arc melting furnace to obtain a plate sample, and then the plate alloy was kept at 1200 ° C in a heat treatment furnace for 24 hours for homogenization annealing. The annealed alloy was then cold rolled with a reduction of 75% to reduce the alloy thickness from 6 mm to 1.5 mm.

[0060] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100°C for 5 minutes and then taken out and water-cooled.

[0061] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (b) The remaining samples were subjected to subsequent oxidation and other tests.

[0062] Comparative Example 3

[0063] The atomic percentages of Cr: 10.04%, Mo: 15.32%, W: 2.15%, Al: 2%, and the balance Ni are converted into mass percentages and weighed.

[0064] Then, the above raw materials are placed in a vacuum induction arc melting furnace for melting and preparation according to their melting points (those with similar melting points are placed in one tank). First, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4 to 6 times. Electromagnetic stirring must be accompanied during the preparation process. The alloy ingot is cast in a copper mold in a vacuum induction arc melting furnace to obtain a plate-shaped sample.

[0065] The plate alloy was then placed in a heat treatment furnace at 1200 °C for 24 h for homogenization annealing, and then the annealed alloy was cold rolled with a reduction of 75% to reduce the alloy thickness from 6 mm to 1.5 mm.

[0066] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100 °C for 5 min and then taken out and water-cooled.

[0067] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (c) The remaining samples were subjected to subsequent oxidation and other tests.

[0068] Comparative Example 4

[0069] The atomic percentages of Cr: 10.04%, Mo: 15.32%, W: 2.15%, Ti: 1.5%, Al: 0.5%, and the balance Ni are converted into mass percentages and the single-substance raw materials are weighed.

[0070] Then, the sponge Ti and the above raw materials are placed in different slots of the vacuum induction arc melting furnace for melting and preparation according to their different melting points (those with similar melting points are placed in one slot). First, the sponge titanium is melted 1-2 times to remove the nitrogen in the furnace to prevent the generation of TiN in the original structure. After removing the nitrogen in the furnace, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4-6 times, and electromagnetic stirring must be accompanied during the preparation process. The alloy ingot is cast in a copper mold in a vacuum induction arc melting furnace to obtain a plate-shaped sample.

[0071] The plate alloy was then kept at 1200°C for 24 hours in a heat treatment furnace for homogenization annealing, and then the annealed alloy was cold rolled with a reduction of 75% to reduce the thickness of the alloy from 6 mm to 1.5 mm.

[0072] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100°C for 5 minutes and then taken out and water-cooled.

[0073] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (b) The remaining samples were subjected to subsequent oxidation and other tests.

[0074] Comparative Example 5

[0075] The atomic percentages of Cr: 10.04%, Mo: 15.32%, W: 2.15%, Ti: 0.5%, Al: 1.5%, and the balance Ni are converted into mass percentages and the single-substance raw materials are weighed.

[0076] Then, the sponge Ti and the above raw materials are placed in different slots of the vacuum induction arc melting furnace for melting and preparation according to their different melting points (those with similar melting points are placed in one slot). First, the sponge titanium is melted 1-2 times to remove the nitrogen in the furnace to prevent the generation of TiN in the original structure. After removing the nitrogen in the furnace, the metal elements with similar melting points are melted together, and then the alloy ingots are melted together for 4-6 times, and electromagnetic stirring must be accompanied during the preparation process. The alloy ingot is cast in a copper mold in a vacuum induction arc melting furnace to obtain a plate-shaped sample.

[0077] The plate alloy was then kept at 1200°C for 24 hours in a heat treatment furnace for homogenization annealing, and then the annealed alloy was cold rolled with a reduction of 75% to reduce the thickness of the alloy from 6 mm to 1.5 mm.

[0078] Finally, the cold-rolled alloy was subjected to recrystallization annealing at 1100°C for 5 minutes and then taken out and water-cooled.

[0079] Finally, some samples were cut off for surface grinding and polishing, and then the alloy structure was observed using a scanning electron microscope to obtain Figure 1 (b) The remaining samples were subjected to subsequent oxidation and other tests.

[0080] Depend on Figure 1 It can be seen that the alloy of the embodiment of the present invention is equiaxed crystal and the structure of the alloy prepared in the comparative example is not much different.

[0081] In order to obtain the oxidation kinetics curve of the alloy prepared by the present invention, the alloy samples after heat treatment and water cooling of the embodiments and comparative examples 1-5 were placed in an alumina crucible and oxidized in a heat treatment furnace at 1100°C and 1000°C for 1, 2, 5, 10, 20, 50, 80, and 100 hours, then taken out for air cooling and the weight was measured using a high-precision balance. In order to prevent the weight of the crucible from changing during the oxidation process, the crucible needs to be roasted for 100 hours before the oxidation experiment begins. After obtaining the oxidation mass increment, the oxidation kinetics curve is drawn, such as Figure 2 .

[0082] In order to obtain the oxide species of the alloy prepared by the present invention, the alloy samples of the embodiment and comparative examples 1-3 after heat treatment and water cooling were placed in a heat treatment furnace at 1100°C and 1000°C for oxidation for 100 hours, and then taken out for air cooling. Finally, the obtained oxidized samples were tested using an X-ray diffractometer to obtain Figure 3 (a), (b), Analysis of the types of oxides on the surface of the oxidized sample.

[0083] In order to analyze the oxidation cross-section of the alloy prepared by the present invention, the samples of Examples and Comparative Examples 1-3 were cut into longitudinal sections after being oxidized at 1100°C for 100 h, and then ground and polished. The oxidation cross-section of the alloy was observed by layering using a scanning electron microscope and an energy spectrum analyzer. Figure 4 , analyze the oxidation mechanism.

[0084] Depend on Figure 2 It can be seen that the oxidation weight gain of the nickel-based high-temperature alloy prepared in the embodiment of the present invention after oxidation at 1100°C and 1000°C for 100 h is the lowest, and the oxidation weight gain is greatly reduced compared with the comparative example.

[0085] Depend on Figure 3 It can be seen that Al2O3 and TiO2 exist in the oxidation product of the nickel-based high-temperature alloy prepared in the embodiment of the present invention.

[0086] Depend on Figure 4 It can be seen that the nickel-based high-temperature alloy prepared in the embodiment of the present invention has a more continuous chromium oxide layer on the surface of the alloy after being oxidized at 1100 ° C for 100 h compared with the oxidized alloys of Comparative Examples 1-3. This is because the addition of Ti element can promote the diffusion of Cr element, so that a continuous chromium oxide layer is formed on the surface of the oxidized sample, which better protects the alloy matrix. In addition, there is obvious oxide peeling on the oxidized surface of Comparative Example 2, while there is almost no oxide layer peeling on the oxidized surface of the embodiment. This is because the addition of Al element can inhibit the formation of TiN and form an Al2O3 inner oxide layer at the same time, improve the combination of the oxide film and the alloy matrix, prevent the oxide film from peeling, and enhance the protection of the alloy matrix.

[0087] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A Haynes 244 alloy with Ti and Al elements added and having excellent high temperature oxidation resistance, characterized in that: The addition amounts of Ti and Al in the Haynes 244 alloy to which Ti and Al elements are added are Ti: 1%, Al: 1% by atomic percentage; the oxidation weight gain of the Haynes 244 alloy to which Ti and Al elements are added after oxidation at 1100° C. for 100 h is less than 0.4 mg / mm 2 ; After oxidation at 1000 ℃ for 100 h, the oxidation weight gain is less than 0.7 mg / mm 2 During the oxidation process, a continuous chromium oxide layer and an aluminum oxide layer can be formed on the surface of the Haynes 244 alloy to which Ti and Al elements are added.

2. The method for preparing a Haynes 244 alloy with added Ti and Al elements having excellent high temperature oxidation resistance according to claim 1, characterized in that: The steps include: S1. Weigh the alloy raw materials according to the composition ratio of Haynes 244 alloy with added Ti and Al elements and having excellent high temperature oxidation resistance as claimed in claim 1 and set them aside; S2 arc-melting the weighed alloy raw material to obtain an alloy ingot, and then pouring it to obtain an alloy sample; S3 taking out the alloy sample, performing homogenization annealing treatment, and then performing cold rolling treatment; S4: performing recrystallization annealing on the alloy sample after cold rolling.

3. The method for preparing the Haynes 244 alloy with added Ti and Al elements having excellent high temperature oxidation resistance according to claim 2, characterized in that: Before smelting the Ti-containing alloy in S2, it is necessary to carry out 1-2 times of sponge Ti smelting in the side cavity of the smelting furnace to fix nitrogen, so that there is no N2 in the smelting furnace when the alloy is smelted.

4. The method for preparing the Haynes 244 alloy with added Ti and Al elements having excellent high temperature oxidation resistance according to claim 2, characterized in that: The homogenization annealing treatment in S3 is specifically: placing the alloy sample into a heat treatment furnace for homogenization annealing treatment at 1180-1220° C. for 24 hours.

5. The method for preparing the Haynes 244 alloy with added Ti and Al elements having excellent high temperature oxidation resistance according to claim 2, characterized in that: The total cold rolling deformation in S3 is not less than 70%, and the deformation in each pass is 2-10%.

6. The method for preparing the Haynes 244 alloy with added Ti and Al elements having excellent high temperature oxidation resistance according to claim 2, characterized in that: The recrystallization annealing temperature in S4 is 1080-1120° C. and the time is 5-7 min.

Citation Information

Patent Citations

  • Precipitation-strengthened nickel-based superalloy and preparation method thereof

    CN114182139A

  • Nickel-base alloy

    US4810467A